Generating driver prioritization for Jabatan Perkhidmatan Awam (JPA) – Malaysia Foresight Institute (MFI) collaboration scenario building workshop using Bayesian technique / Wan Nur Zhulianna Wan Rahmat Asmadi - Wan Rahmat Asmadi, Wan Nur Zhulianna (2015)
Foresight is a systematic attempt of decision making process which will look at the long-term vision regarding the development from the technology, economy and social aspect. For Malaysia context, there are many foresight methodologies that have been implemented since the first involvement of Malaysia in foresight back in the 90s. This project will focus on only prioritization of drivers in a foresight study within the scenario building or prognosis phase under the myForesight approach. Scenario building is a support tool used in the decision making process for the environments of the possible future. Drivers of a foresight study are obtained from the horizon scanning or the diagnosis phase. In Malaysia’s foresight environment, the organization responsible for the nation’s foresight practice is the Malaysian Industry-Government Group for High Technology (MIGHT). Therefore, this project will develop a web-based system that will support the process of prioritizing drivers of a foresight study in Malaysia for the purpose of improving the decision making process in the foresight exercise. This project will apply the use of adaptive Bayesian network algorithm as it is more efficient and the most suitable than some of the possible techniques which have been studied.